Improved hematopoietic differentiation of human pluripotent stem cells via estrogen receptor signaling pathway. Issue 1 (December 2016) - Kim, Hye-Ryun; Lee, Jong-Hee; Heo, Hye-Ryeon; Yang, Se-Ran; Ha, Kwon-Soo; Park, Won; Han, Eun-Taek; Song, Haengseok; Hong, Seok-Ho
Abstract Background Aside from its importance in reproduction, estrogen (E2) is known to regulate the proliferation and differentiation of hematopoietic stem cells in rodents. However, the regulatory role of E2 in human hematopoietic system has not been investigated. The purpose of this study is to investigate the effect of E2 on hematopoietic differentiation using human pluripotent stem cells (hPSCs). Results E2 improved hematopoietic differentiation of hPSCs via estrogen receptor alpha (ER-α)-dependent pathway. During hematopoietic differentiation of hPSCs, ER-α is persistently maintained and hematopoietic phenotypes (CD34 and CD45) were exclusively detected in ER-α positive cells. Interestingly, continuous E2 signaling is required to promote hematopoietic output from hPSCs. Supplementation of E2 or an ER-α selective agonist significantly increased the number of hemangioblasts and hematopoietic progenitors, and subsequent erythropoiesis, whereas ER-β selective agonist did not. Furthermore, ICI 182, 780 (ER antagonist) completely abrogated the E2-induced hematopoietic augmentation. Not only from hPSCs but also from human umbilical cord bloods, does E2 signaling potentiate hematopoietic development, suggesting universal function of E2 on hematopoiesis. Conclusions Our study identifies E2 as positive regulator of human hematopoiesis and suggests that endocrine factors such as E2 influence the behavior of hematopoietic stem cells in various physiological conditions.